IMPLEMENTING SHORTS MOVIES TO IMPROVE THE STUDENTS’ VOCABULARY KNOWLEDGE: A SIMPLE EXPERIMENTAL STUDY - Hilma Safitri; Nur Amalia (Universitas Muhammadiyah Metro, 2025)
This study aims to improve the vocabulary of eighth-grade students by using movies as a medium in learning at SMP Al-Ma’mur.Â By employing a simple experimental study design, incorporating both qualitative and quantitative data, this study explored the impact of movie-based vocabulary instruction.Â Data collection involved pre-tests, post-tests, and some student interviews.Â The participants were 15 junior high school students in grade 8 that were given some pre and post-tests together with the interview for some both qualitative and quantitative data findings. Some data quantitative were calculated to find some significant improvement. While some data qualitative were interpreted based on some theories adopted. The results revealed a statistically significant improvement for the students' vocabulary scores in which the maximum pretest score was < 50 that indicated under the minimum passing score (KKM) /75. While the posttest score was 100 maximums complemented by overwhelmingly positive qualitative feedback regarding the students’ learning experience. The study concludes that utilizing movies as an instructional tool in language classrooms creates a more dynamic and motivating learning environment, thereby promoting effective language acquisition.